ETHICAL COMMITMENTS AND FINANCIAL PERFORMANCE: EVIDENCE FROM PUBLICLY LISTED COMPANIES IN MALAYSIA - Ahmad Firdhauz Zainul Abidin,; Hafiza Aishah Hashim,; Akmalia Mohamad Arif, (Asian Academy of Management Journal, 2017)
This study explores the role of business ethics towards corporate wealth creation and sustainable performance. In the context of Malaysia, the importance of committing to following the highest ethical standards is evidenced by the recommendations and guidelines imposed through the Malaysian Code of Corporate Governance (MCCG) 2012. The perspective from stakeholder theory indicates that commitment towards ethics has multiple, positive impacts to companies. One of the positive impacts, which is a result of being able to gain trust and secure loyalty from their stakeholders, is better financial performance. This study posits that management commitment towards ethics is positively associated with financial performance. Content analysis is used to systematically code and evaluate data from 243 publicly listed firms on the Main Board of Bursa Malaysia in year 2014. The Ethics Commitment Assessments Index (ECAI), which contains 14 items, is used to score commitment towards ethics. Financial performance is represented by return on assets (ROA) and return on equity (ROE). The results show a positive relationship between commitment towards ethics and financial performance. The findings contribute to policy formulation by suggesting that commitment towards ethics should continue to be emphasised by regulators because it is considered by stakeholders in assessing the risk of companies in the capital market.